Cardiovascular Diseases and Non-Alcoholic Fatty Liver Disease: Relationship and Pathogenetic Aspects of Pharmacotherapy - A. V. Nelidova; M. A. Livzan; N. A. Nikolaev; T. S. Krolevets (Столичная издательская компания, 2022)
The association of non-alcoholic fatty liver disease (NAFLD) and cardiovascular risk is currently one of the actively studied areas. The incidence of non-alcoholic fatty  liver disease continues to grow worldwide. In the structure of mortality rate of patients with non-alcoholic fatty  liver disease,  the first place is occupied by cardiovascular events: stroke and myocardial infarction. Studies have shown that the presence of severe liver fibrosis (F3-4) in NAFLD not only increases the risk of cardiovascular diseases (CVD), but also increases the risk  of  overall  mortality  by  69%  due  to mortality from cardiovascular causes. The degree of increased risk is associated with the degree of activity of non-alcoholic steatohepatitis (NASH). Despite the large number of works on this topic, we do not have a clear opinion on the impact on cardiovascular risk, interaction and the contribution of various factors, as well as algorithms for managing patients with non-alcoholic fatty liver disease to reduce the risk of cardiovascular diseases. This article describes the pathogenetic factors of formation of cardiovascular risks in patients with non-alcoholic fatty liver disease, proposed the idea of stratification of cardiovascular risks in these patients, taking into account changes in the structure of the liver (fibrosis) and function (clinical and biochemical activity) and also it describes the main directions of drug therapy, taking into account the common pathogenetic mechanisms for non-alcoholic fatty liver disease and cardiovascular diseases. The role of obesity, local fat depots, adipokines, and endothelial dysfunction as the leading pathogenetic factors of increased cardiovascular risk in patients with NAFLD is discussed. Among pathogenetically justified drugs in conditions of poly and comorbidity, hypolipidemic (statins, fibrates), angiotensin II receptor antagonists, beta-blockers, etc. can be considered. According to numerous studies, it becomes obvious that the assessment of cardiovascular risks in patients with NAFLD will probably allow prescribing cardiological drugs, selecting individualized therapy regimens, taking into account the form of NAFLD, and on the other hand, building curation taking into account the identified cardiovascular risks.